2020
DOI: 10.1038/s41598-020-75508-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the long-term changes in the Madden Julian Oscillation using machine learning

Abstract: The Madden Julian Oscillation (MJO), the dominant subseasonal variability in the tropics, is widely represented using the Real-time Multivariate MJO (RMM) index. The index is limited to the satellite era (post-1974) as its calculation relies on satellite-based observations. Oliver and Thompson (J Clim 25:1996–2019, 2012) extended the RMM index for the twentieth century, employing a multilinear regression on the sea level pressure (SLP) from the NOAA twentieth century reanalysis. They obtained an 82.5% correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 36 publications
4
25
0
Order By: Relevance
“…11) shows highest value of correlation in November 41.3% and January 19.8% of the meteorological stations. One of the reasons of this results that are consistent with other research, could be that RMM1 describes the situation when a MJO produces an enhanced convection at the Maritime Continent while RMM2 has enhanced convection over the Paci c Ocean90,91 closer to California State. In addition it is remarkable that the correlated stations with temperatures, in June, are located mainly both in coastal areas of San Francisco, Santa Barbara and Los Angeles and mountainous areas of Auburn, Oroville and Susanville Dasgupta et al (2020).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…11) shows highest value of correlation in November 41.3% and January 19.8% of the meteorological stations. One of the reasons of this results that are consistent with other research, could be that RMM1 describes the situation when a MJO produces an enhanced convection at the Maritime Continent while RMM2 has enhanced convection over the Paci c Ocean90,91 closer to California State. In addition it is remarkable that the correlated stations with temperatures, in June, are located mainly both in coastal areas of San Francisco, Santa Barbara and Los Angeles and mountainous areas of Auburn, Oroville and Susanville Dasgupta et al (2020).…”
supporting
confidence: 89%
“…One of the reasons of this results that are consistent with other research, could be that RMM1 describes the situation when a MJO produces an enhanced convection at the Maritime Continent while RMM2 has enhanced convection over the Paci c Ocean90,91 closer to California State. In addition it is remarkable that the correlated stations with temperatures, in June, are located mainly both in coastal areas of San Francisco, Santa Barbara and Los Angeles and mountainous areas of Auburn, Oroville and Susanville Dasgupta et al (2020). found that the occurrences of MJO activity at RMM phase locations 4, 5 and 6 during boreal winter are related to the PDO index, particularly in the negative phases.…”
supporting
confidence: 89%
“…Synthetic data can also be generated using ML applied to observations and reanalysis to extend the availability of labeled data to train a CNN on S2D timescales. Dasgupta et al (2020) recently demonstrated this technique with a CNN-based approach that improved historical reconstructions of the MJO, which was then used to explore its decadal variability. This type of semi-supervised approach can extend S2D predictability by increasing the availability of labeled data.…”
Section: Narrativementioning
confidence: 99%
“…There could be various reasons for these issues, particularly in India, such as the complex, non-linear and turbulent weather in the tropical regions and the usage of parameterization schemes generating precipitation in the model. Other than numerical models, statistical and feature selection-based Artificial Neural Network (ANN) models have been used in the past to predict rainfall in different time scales with some success [9], [10] . These models employ two popular concepts: feature selection and then prediction using statistical or simple machine learning algorithms [9], [11]- [13].…”
Section: Introductionmentioning
confidence: 99%